1999
DOI: 10.1016/s0014-5793(98)01723-2
|View full text |Cite
|
Sign up to set email alerts
|

Apocynin increases glutathione synthesis and activates AP‐1 in alveolar epithelial cells

Abstract: Apocynin (4-hydroxy-3-methoxy-acetophenone) is a potent intracellular inhibitor of superoxide anion production in neutrophils. In this study, we studied the effect of apocynin on the regulation of the antioxidant glutathione (GSH) and activation of the transcription factor AP-1 in human alveolar epithelial cells (A549). Apocynin enhanced intracellular GSH by increasing Q Q-glutamylcysteine synthetase activity in A549 cells. Apocynin also increased the expression of Q Q-GCS heavy subunit mRNA. This was associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 30 publications
(41 reference statements)
4
39
0
Order By: Relevance
“…Finally, our studies also provide preliminary evidence that NADPH oxidase may be involved in an oxygen radical-dependent killing mechanism during P. falciparum infection (47). Previous studies have shown that apocynin targets NADPH oxidase and that the antioxidant property of apocynin results from an increase in GSH biosynthesis (48). Even though apocynin has been shown to specifically target NADPH oxidase, the higher concentrations required may also indicate other unknown, "off-target" effects.…”
Section: Discussionsupporting
confidence: 51%
“…Finally, our studies also provide preliminary evidence that NADPH oxidase may be involved in an oxygen radical-dependent killing mechanism during P. falciparum infection (47). Previous studies have shown that apocynin targets NADPH oxidase and that the antioxidant property of apocynin results from an increase in GSH biosynthesis (48). Even though apocynin has been shown to specifically target NADPH oxidase, the higher concentrations required may also indicate other unknown, "off-target" effects.…”
Section: Discussionsupporting
confidence: 51%
“…Conversely, some compounds such as 4′-HC, curcumin, and 2-HE elevated intracellular GSH levels in HL-60 and PC-3 cells. This accumulation is likely due to stimulation of GSH synthesis, as has been shown with apocynin and curcumin in A549 cells [51,52]. Interestingly, curcumin, 4′-HC and apocynin have in common the presence of a hydroxyl group in position 4 of a phenolic moiety.…”
Section: Discussionmentioning
confidence: 67%
“…The plant-derived phenolic antioxidant apocynin (4-hydroxy-3-methoxyacetophenone) also induces GSH synthesis in human alveolar epithelial cells [79]. These effects of phenolic antioxidants are associated with AP-1 transactivation [57,60,102].…”
Section: At Transcriptional Levelmentioning
confidence: 99%